In vivo imaging of microglial activation by positron emission tomography with [11 C]PBR28 in the 5XFAD model of Alzheimer's disease - Mirzaei,N; Tang,SP; Ashworth,S; Coello,C; Plisson,C; Passchier,J; Selvaraj,V; Tyacke,RJ; Nutt,DJ; Sastre,M (GLIA, 2016)
Microglial activation has been linked with deficits in neuronal function and synaptic plasticity in Alzheimer's disease (AD). The mitochondrial translocator protein (TSPO) is known to be upregulated in reactive microglia. Accurate visualization and quantification of microglial density by PET imaging using the TSPO tracer [11C]-R-PK11195 has been challenging due to the limitations of the ligand. In this study, it was aimed to evaluate the new TSPO tracer [11C]PBR28 as a marker for microglial activation in the 5XFAD transgenic mouse model of AD. Dynamic PET scans were acquired following intravenous administration of [11C]PBR28 in 6-month-old 5XFAD mice and in wild-type controls. Autoradiography with [3H]PBR28 was carried out in the same brains to further confirm the distribution of the radioligand. In addition, immunohistochemistry was performed on adjacent brain sections of the same mice to evaluate the co-localization of TSPO with microglia. PET imaging revealed that brain uptake of [11C]PBR28 in 5XFAD mice was increased compared with control mice. Moreover, binding of [3H]PBR28, measured by autoradiography, was enriched in cortical and hippocampal brain regions, coinciding with the positive staining of the microglial marker Iba-1 and amyloid deposits in the same areas. Furthermore, double-staining using antibodies against TSPO demonstrated co-localization of TSPO with microglia and not with astrocytes in 5XFAD mice and human post-mortem AD brains. The data provided support of the suitability of [11C]PBR28 as a tool for in vivo monitoring of microglial activation and assessment of treatment response in future studies using animal models of AD